Amelioration of Radiation-Induced Cell Death in Neuro2a Cells by Neutralizing Oxidative Stress and Reducing Mitochondrial Dysfunction Using N-Acetyl-L-Tryptophan. (26th November 2022) - Kumar, Ravi; Kumari, Pratibha; Pandey, Swapnil; Singh, Shravan Kumar; Kumar, Raj
Abstract : The deleterious effects of ionizing radiation on the central nervous system (CNS) are poorly understood. Radiation exposure during an accidental nuclear explosion, nuclear war, or radiotherapy causes severe brain damage. As a result, the current work is carried out to assess the radioprotective potential of N-acetyl-L-tryptophan (L-NAT) in neuronal cells. Radiation-induced cell death and its amelioration by L-NAT pretreatment were investigated using MTT, SRB, CFU, and comet assays. Flow cytometric and microscopic fluorescence assays were used to investigate radiation-induced oxidative stress, alteration in mitochondrial redox, Ca 2+ homeostasis, depolarization of mitochondrial membrane potential, and its prevention with L-NAT pretreatment. Western blot analysis of Caspase-3, γ -H2aX, p53, ERK-1/2, and p-ERK-1/2 expression was carried out to identify the effects of L-NAT pretreatment on radiation-induced apoptosis and its regulatory proteins expression. The study demonstrated (MTT, SRB, and CFU assay) significant (~80%; p <0.001%) radioprotection in irradiated (LD50 IR dose) Neuro2a cells that were pretreated with L-NAT. In comparison to irradiated cells, L-NAT pretreatment resulted in significant (p <0.001%) DNA protection. A subsequent study revealed that L-NAT pretreatment of irradiated Neuro2a cells establishes oxidative stress by increasing antioxidant enzymes and mitochondrial redox homeostasis by inhibiting Ca 2+ migration from the cytoplasm to the mitochondrial matrix and thus protects the mitochondrial membrane hyperpolarization. Caspase-3 and γ -H2aX protein expression decreased, while p-ERK1/2 and p53 expression increased in L-NAT pretreated irradiated cells compared to irradiated cells. Hence, L-NAT could be a potential radioprotective that may inhibit oxidative stress and DNA damage and maintain mitochondrial health and Ca 2+ levels by activating p-ERK1/2 and p53 expression in Neuronal cells.